2019
DOI: 10.1136/annrheumdis-2019-215886
|View full text |Cite|
|
Sign up to set email alerts
|

Knee osteoarthritis risk in non-industrial societies undergoing an energy balance transition: evidence from the indigenous Tarahumara of Mexico

Abstract: Non-industrial societies with low energy balance levels are expected to be less vulnerable than industrial societies to diseases associated with obesity including knee osteoarthritis. However, as non-industrial societies undergo rapid lifestyle changes that promote positive energy balance, individuals whose metabolisms are adapted to energetic scarcity are encountering greater energy abundance, increasing their propensity to accumulate abdominal adipose tissue and thus potentially their sensitivity to obesity-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 47 publications
0
27
0
Order By: Relevance
“…Obesity creates an abnormal loading environment for weight-bearing joints and may contribute to the pathogenesis of KOA [48]. Alternatively, the increased risk of KOA may be caused by the positive energy balance and metaflammation associated with obesity [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity creates an abnormal loading environment for weight-bearing joints and may contribute to the pathogenesis of KOA [48]. Alternatively, the increased risk of KOA may be caused by the positive energy balance and metaflammation associated with obesity [49].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the increased risk of KOA may be caused by the positive energy balance and metaflammation associated with obesity [49]. Although BMI has been illustrated as an important predictor of KOA [50], Wallace et al (2019) [48] reported that increased abdomen size is associated with a greater risk of radiographic KOA than high BMI. Further studies are required to determine whether BMI, waist circumference, or metabolic syndrome comprehensively influences KOA risk due to mechaflammation and metaflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity creates an abnormal loading environment for weight-bearing joints and may contribute to the pathogenesis of KOA [48]. Alternatively, the increased risk of KOA may be caused by the positive energy balance and meta ammation associated with obesity [49].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the increased risk of KOA may be caused by the positive energy balance and meta ammation associated with obesity [49]. Although BMI has been illustrated as an important predictor of KOA [50], Wallace et al (2019) [48] reported that increased abdomen size is associated with a greater risk of radiographic KOA than high BMI. Further studies are required to determine whether BMI, waist circumference, or metabolic syndrome comprehensively in uences KOA risk due to mecha ammation and meta ammation.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity may also contribute to the pathogenesis of KOA by promoting chronic low-grade systemic in ammation or inducing mechanical damage to joint tissues, which in turn may lead to local in ammation. Together, these factors may weaken and degrade joint tissues [35]. Alternatively, the increased risk of KOA may be caused by the positive energy balance and meta ammation associated with obesity [36].…”
Section: Discussionmentioning
confidence: 99%